ACTH-secreting medullary thyroid cancer: a case series - Wijewardene, Ayanthi A (Endocrinol Diabetes Metab Case Rep, 2017)
Medullary thyroid cancer (MTC) is a rare neuroendocrine tumour that originates from the parafollicular cells of the thyroid gland. The most common presentation of MTC is with a single nodule; however, by the time of diagnosis, most have spread to the surrounding cervical lymph nodes. Cushing’s syndrome is a rare complication of MTC and is due to ectopic adrenocorticotrophic hormone (ACTH) secretion by tumour cells. Cushing’s syndrome presents a challenging diagnostic and management issue in patients with MTC. Tyrosine kinase inhibitors (TKI) previously used for the management of metastatic MTC have become an important therapeutic option for the management of ectopic ACTH in metastatic MTC. The article describes three cases of ectopic ACTH secretion in MTC and addresses the significant diagnostic and management challenges related to Cushing’s syndrome in metastatic MTC. LEARNING POINTS: Medullary thyroid cancer (MTC) is a rare neuroendocrine tumour. Cushing’s syndrome is a rare complication of MTC that has a significant impact on patients’ morbidity and mortality. Tyrosine kinase inhibitors (TKI) provide an important therapeutic option for the management of ectopic ACTH in metastatic MTC.